PENGELOLAAN PROGRAM SANITASI LINGKUNGAN BERBASIS MASYARAKAT DI KOTA SEMARANG TAHUN 2012-2015. STUDI KASUS: KAMPUNG BUSTAMAN KELURAHAN PURWODINATAN KECAMATAN SEMARANG TENGAH - Angga Rattafary; Fitriyah .; Priyatno Harsasto (Journal of Politic and Government Studies, 2016)
Poor environmental sanitation remains one of the sanitation problem in Indonesia, including Semarang .The compliance of good sanitation was enforced in major cities in indonesia. Semarang city that ranked as the worst environmental sanitation in second place, has made an Urban Community-Based Sanitation program (SPBM), as the concern to sanitation problem, that one of them has been implemented in Bustaman.Communal sanitation program involved by the government, local community, and private parties. Either agreement or networking with other parties will overcome the problem of limited government in implementating program. This study aimed to reveal the management system, role of government, society, and private parties, also networking concept in management program communal sanitation at Kampung Bustaman.This research is a descriptive qualitative in-depth interviews and observation.The subjects of this study amounted to two as key informants and two as triangulation informantswhere purposive sampling technique was used to determine samples.The results showed management of communal sanitation program had run well. It proved by the institutional tool that arranged by all the parties in common; the pioneering leadership, that government as the main responsible of the running program; the common comprehension of technical planning and implementation; and the management tool of communal sanitation program. Involvement of three actors has been implemented sustainably, so that providing beneficial results for all the parties. In this good condition, the model of communal sanitation that used in Bustaman should be adopted by other urban areas, where have the same condition.